Li4SnS4 and Li4SnSe4: Simulations of Their Structure and Electrolyte Properties. Issue 1 (1st January 2017) - Al-Qawasmeh, Ahmad; Howard, Jason; Holzwarth, N. A. W.
Abstract : Recent experimental literature reports the solid state electrolyte properties of Li4 SnS4 and Li4 SnSe4, identifying interesting questions regarding their structural details and motivating our first principles simulations. Together with Li4 GeS4, these materials are all characterized by the orthorhombic space group Pnma and are found to be isostructural. They have a ground state crystal structure (denoted Li4 SnS 0 4 ) having interstitial sites in void channels along the c -axis. They also have a meta-stable structure (denoted Li4 SnS*4 ) which is formed by moving one fourth of the Li ions from their central sites to the interstitial positions, resulting in a 0.5 Å contraction of the a lattice parameter. Relative to their ground states, the meta-stable structures are found to have energies 0.25 eV, 0.02 eV, and 0.07 eV for Li4 GeS*4, Li4 SnS*4, and Li4 SnSe*4, respectively. Consistent with these simulation results, the ground state forms for Li4 GeS 0 4, Li4 SnS 0 4 and Li4 SnSe 0 4 and the meta-stable form for Li4 SnS*4 have been reported in the experimental literature. In addition, simulations of Li ion migration in these materials are also investigated.